Investigating the Effects of Chopped Basalt Fiber on the Performance of Porous Asphalt Mixture. (2nd July 2019) - Wang, Sheng; Kang, Aihong; Xiao, Peng; Li, Bo; Fu, Weili
Abstract : Porous asphalt mixture is a type of asphalt mixture with good drainage. However, it has poor tensile strength performance and durability. Chopped basalt fibers (CBF) have been proved to be an effective additive to improve the mechanical and fatigue performance of asphalt mixtures, but little attention has been paid on porous asphalt mixture. This paper examined the effect of chopped basalt fibers with different lengths (nonfiber, 3 mm, 6 mm, 9 mm, and 12 mm) and contents (3% and 4%) on the performance of the porous asphalt mixture. A series of tests were conducted to figure out the optimum fiber length and content, including draindown test, cantabro abrasion test, freeze-thaw split tensile test, wheel tracking test, low-temperature cracking resistance test, and four-point bending beam test. Thereafter, indirect tensile tests at different temperatures were conducted to investigate the tensile strength properties of porous asphalt mixtures with optimum fiber length and content. Besides, the macroscopic and microscopic morphology of fracture sections of the samples after indirect tensile tests were studied by using a single-lens reflex (SLR) camera and scanning electron microscopy (SEM) so as to further explore the reinforced mechanism of chopped basalt fibers. The results show that the addition of chopped basalt fibers can generally improve the performance of porous asphalt mixture since chopped basalt fibers form a three-dimensional network structure in the porous asphalt mixture.